Histochemical investigation of different organce of genus sesbania of marathwada region in maharashtra - Momin, R K; B, Kadam V (Journal of Phytology, 2011)
The histochemical studies of leaves and wood of Sesbania grandiflora, Sesbania bispinosa and Sesbania cannabina are medicinally important plants of Marathwada region in Maharashtra. For histochemical studies the free hand sections of leaves and wood were taken and treated with the respective reagent in localize components, viz. starch, protein, tannin, saponin, fat, glucosides and alkaloids in the tissues.